Determinants of Dividend Payout Decisions of FMCG Companies in India : A Study of Firm-Specific Characteristics of Selected Companies - Kaur, Navleen (Indian Journal of Finance, 2025)
Purpose : Designing an effective dividend policy is crucial for corporate finance as it impacts all stakeholders. This study examined the determinants of dividend payout decisions for fast-moving consumer goods (FMCG) companies in India. Research Methodology : This study utilized quantitative data drawn from the published reports of 12 NIFTY FMCG companies and the PROWESSIQ database of the Center for Monitoring Indian Economy (CMIE) for 2009 to 2022. The analysis involved descriptive statistics, correlations, regression diagnostics tests, and panel data regression of 168 firm-year observations conducted using STATA software. Findings : The random effects model, with an R2 value of 48.89%, indicated a good fit. Profitability, investment opportunities, and company size significantly and positively affected dividend payouts. Conversely, business risk and book value per share exhibited a negative and significant relationship with the dividend payout ratio of the analyzed companies. Practical Implications : Overall, this study served as a foundation for decision-making and future research targeting the FMCG sector to generalize the factors influencing dividend payout decisions in these companies. Originality : This study offered a fresh perspective by focusing on FMCG companies within the NIFTY FMCG Index, a sector that has received limited research attention in India. As far as the author knows, this research is the first to pinpoint the factors influencing dividend payout decisions for NSE-listed FMCG companies and included in the NIFTY FMCG Index by employing panel data analysis. It reviewed previous studies spanning several decades and incorporated various variables discussed in the literature, offering a unique contribution to the field.